INNOVATIVE TECHNOLOGIES AND THEIR APPLICATION IN SPORTS (Neo Science Peer Reviewed Journal, 2023)
The theory and practice of physical culture are closely related to innovation. This is the development of a new concept of physical education of professional athletes, the creation of an updated training system, the transition from archaic methods to advanced methods of supporting the activities of athletes at all stages.